Enhancing Marketing Strategy Effectiveness in Fintech: The Interplay of Big Data Analysis, Digital Engagement, and Market Adaptability - Shafiq Ur Rehman; Saima Hassan; Maooz Rafay; Aasim Munir Dad; Sajjad Nawaz Khan (Journal of Management Practices, Humanities and Social Sciences, 2023)
This study explores the dynamics of marketing strategy effectiveness in the fintech sector, emphasizing the roles of big data analysis, digital engagement, and market adaptability. In an era where technological advancements and consumer preferences evolve rapidly, understanding these factors is crucial for the success of marketing strategies. We employed a quantitative research methodology, distributing a structured questionnaire among professionals in the fintech industry. The collected data was analyzed using statistical techniques, including reliability tests, factor analysis, and regression models to test the formulated hypotheses. The findings revealed that big data analysis significantly enhances marketing strategy effectiveness by enabling data-driven decision-making. Digital engagement was identified as a key factor in strengthening customer relationships and brand loyalty, thereby improving marketing outcomes. Furthermore, market adaptability emerged as a crucial element, highlighting the importance of agility and responsiveness to market changes for effective marketing strategies. This study contributes to the existing literature by providing a comprehensive understanding of the synergistic effects of these variables on marketing strategy effectiveness in fintech. It offers valuable insights for fintech companies and policymakers, emphasizing the need for technological and adaptive capabilities in marketing. The study's limitations suggest avenues for future research, including a broader geographical scope and the exploration of additional influencing factors.